Analysis of MICE Tour Package Usage in Malang City - Yulianto, Irwan (Politeknik Pariwisata NHI Bandung, 2025)
This research aims to analyze the use of MICE (Meetings, Incentives, Conferences, and Exhibitions) tour packages in Malang City and their impact on the consumption patterns of business tourists and bleisure preferences. The identified issues include the form of MICE tour package usage in the implementation of MICE activities in Malang City, the impact of MICE tour package usage on business tourist visits, and the bleisure trend that has not yet been widely facilitated by tour service providers. This bleisure trend indicates that business travelers tend to extend their stay to engage in additional leisure activities after their business events are completed. However, the lack of MICE tour packages integrated with bleisure activities can reduce the comfort and effectiveness of business travelers' trips. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method. The research sample consists of 150 respondents who are business travelers and MICE tourism service providers in the city of Malang. The analysis results show that the use of MICE tour packages significantly affects the consumption patterns of business travelers and bleisure preferences. Bleisure preferences have been proven to mediate the influence of MICE tour package usage on the consumption patterns of business travelers. This means that the more attractive and complete the MICE tour packages are, the greater the incentive for business travelers to engage in bleisure activities, thereby increasing tourist consumption during their visit. The findings of this research emphasize that tourism service providers in Malang City need to develop more integrated and flexible MICE tour packages to support bleisure activities. Thus, the continuously increasing bleisure trend can be utilized to extend the stay of business travelers and promote sustainable tourism economic growth.